Wrist Exoskeleton Device with a Novel Cable Drive Solution - Minh Thong NGUYEN; Van Hau TRAN; Tan Hung HUYNH; Viet Anh Dung CAI; Thanh Tung LE (Journal of Technical Education Science, 2024)
This paper presents the design of a lower limb exoskeleton made for the purpose of wrist joint rehabilitation. The authors use the exoskeleton structure in order to cope with the user’s upper-limb kinematics and to provide motion to the wrist joint when the arm is in any possible spatial configuration. To reduce the inertia of the mechanical structure, the motors are fixed at the back of the user and the power transmission is realized via a cable drive transmission. Two elastic cables are used to control the flexion/extension movement of the wrist joint. The tensions inside the elastic cables are controlled within the use of 2 torque sensors. By using two DC motors, the actuation unit can act like human tendons and provides more natural assistance motion. At the output axis, a third torque sensor is used to allow the control of the interaction between the mechanism and the user’s wrist joint.